Desenvolvimento e avaliação de software para uso no acolhimento com classificação de risco em pediatria - Felipe, Gilvan Ferreira (2016)
Risk classification (RC) is a relevant strategy for assessing and stratifying the risk and vulnerabilities of patients treated at emergency and emergency units, enabling to identify which cases require immediate assistance and which can wait for safe care. In addition, the recognition of technological evolution, especially in the computational field, stimulates the idea that the use of such technologies in the daily life of health services can contribute to improving the quality and safety of the service provided. The objective was to develop and evaluate a software about the process of RC in pediatrics. Methodological study developed in three stages: Step 1 - Software development; Step 2 - Evaluation of the technical quality and functional performance of the software through the analysis of the characteristics covered by ISO / IEC 25010, carried out by eight specialists in the area of informatics and 13 in the area of nursing; and Step 3 - Evaluation of the agreement of the software in relation to the printed protocol, performed by three nurses with experience in RC. Data analysis was performed using descriptive statistics using absolute and relative frequencies and inferential statistics using the Kendall coefficient of agreement (W), with the aid of Microsoft Office software Excel®, Statistical Package for Social Sciences (SPSS) version 20.0 and R. The ethical aspects were respected and the study was approved by the Research Ethics Committee of the Federal University of Ceará and received approval on opinion nº 1,327,959 / 2015 . For the development of the proposed software, we used the prescriptive process model of software engineering called Incremental Model, the language used for the development was CSharp (C #) and the database chosen was Microsoft® SQL Server® 2008 R2. The results obtained from the evaluation of the software developed for this study reveal that it was adequate in all characteristics analyzed and was indicated as very appropriate and / or completely appropriate by more than 70.0% of the evaluations of the specialists in computer science, as follows: functional adequacy - 100.0%; Reliability - 82.6%; Usability - 84.9%; Performance efficiency - 93.4%; Compatibility - 85.0%; Security - 91.7%; Maintainability - 95.0%; and portability - 87.5%, as well as by the nursing specialists: functional adequacy - 96.2%; Reliability - 88.5%; Usability - 98.7%; Performance efficiency - 96.2%; Compatibility - 98.1%; Security - 100.0%. The results of the risk classification generated by the use of the software, when compared to those generated from the use of the printed protocol, indicated a total agreement by two judges (W = 1,000; p <0.001) and very high agreement by another one (W = 0.992, p <0.001). The results allowed to conclude that the Software for ACCR in Pediatrics, developed in this study, was considered adequate in relation to technical quality and functional performance. In addition, the software presented high agreement in comparison with the printed protocol, currently used to perform the ACCR in the city of Fortaleza, evidencing its potential safety for the assistance of the nurses involved in conducting the RC in pediatrics.